The cellular phone industry in Malaysia toward IMT-2000. - Rahman, T.A (IEEE Communications magazine)
Explosive growth of the cellular phone industry in Malaysia has been witnessed in the 1990s. Eight nationwide cellular phone operators with different technology bases exist in a single market. This article provides an overview of the telecommunications industry, especially the cellular phone sector, and also the activities on IMT-2000 in Malaysia